2008
DOI: 10.1007/978-3-540-69389-5_13
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of Asymmetric Mutational Pressure and Selection Pressure Around the Universal Genetic Code

Abstract: Abstract.One of hypotheses explaining the origin of the genetic code assumes that its evolution has minimised the deleterious effects of mutations in coded proteins. To estimate the level of such optimization, we calculated optimal codes for genes located on differently replicating DNA strands separately assuming the rate of amino acid substitutions in proteins as a measure of code's susceptibility to errors. The optimal code for genes located on one DNA strand was simultaneously worse than the universal code … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
2
1

Relationship

5
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…Mutations occurring in biological DNA sequences are not completely random but are a result of coevolution between mutational pressure with selection constraints around the genetic code [2,5] and can be optimized to some extent during evolution ( [6]). On one hand, most mutations are deleterious and generate energetic costs of their repairing, therefore a tendency to decrease the mutation rate should exist.…”
Section: Introductionmentioning
confidence: 99%
“…Mutations occurring in biological DNA sequences are not completely random but are a result of coevolution between mutational pressure with selection constraints around the genetic code [2,5] and can be optimized to some extent during evolution ( [6]). On one hand, most mutations are deleterious and generate energetic costs of their repairing, therefore a tendency to decrease the mutation rate should exist.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have also showed that no direct selection for the error minimization 437 was necessary to produce the genetic codes with this property, which could have evolved 438 as a result of gene duplications of adaptors and charging enzymes [Massey, 2015, Massey, 439 2016. Interestingly, the optimization of biological systems to minimize the harmful 440 effects of mutations does not have to require changes in the genetic code because the 441 mutational pressure can be subjected to this optimization around the fixed genetic 442 code [Dudkiewicz et al, 2005, Mackiewicz et al, 2008, B lażej et al, 2015 2017].…”
mentioning
confidence: 99%
“…The minimization of mutation errors is important from a biological point of view, because it protects organisms against losing genetic information. Then, the reduction of the mutational load seems favoured by biological systems and can occur directly at the level of the mutational pressure [45][46][47][48][49]. Nevertheless, in the global scale, the SGC shows a general tendency to error minimization [37,44], which is more exhibited by its alternative versions [50], evolved later.…”
Section: Discussionmentioning
confidence: 99%